A new species of Griffinia (Amaryllidaceae) from Espírito Santo state, Brazil, and reassessment of Griffinia concinna - Campos-Rocha, Antonio; Meerow, Alan William; Semir, João; Dutilh, Julie Henriette Antoinette (Phytotaxa, 2017)
Griffinia capixabae, a new species of Amaryllidaceae restricted to the mountainous region of the state of Espírito Santo, Brazil, and classified as endangered, is described and illustrated herein. It is morphologically similar to G. intermedia, but can be distinguished by its completely free spathe bracts, smaller overall perigone length, longer hypanthium, the lack of spots on the center of the sepals and petals, and smaller seeds. The new species is illustrated with photographs and a drawing; geographical distribution, habitat, phenology and conservation status are discussed. The paper also reassesses G. concinna as a valid species name, with a more detailed description and distribution including new records for the state of Espírito Santo. An identification key for the species with larger flowers and leaves of the genus is provided.